Crypto Asset Insurance for Physical Trading of Crypto Assets on the Crypto Asset Futures Exchange - Ade Rizki Saputra (Formosa Journal of Sustainable Research, 2023)
Crypto assets are now recognized as commodities on the Crypto Asset Futures Exchange, and in creating a system to enable trading of crypto assets, the Commodity Futures Trading Regulatory Agency has provided certain guidelines for the parties involved to ensure that trading can be carried out without problems. However, the Commodity Futures Trading Supervisory Agency does not provide specifications regarding crypto asset insurance, which means that insurance companies must make crypto asset insurance in accordance with existing laws and regulations, namely the Commercial Law Book, Law Number 40 of 2014 concerning Insurance , as well as the Financial Services Authority Regulations as the body that regulates insurance. Thus, this paper aims to find out how crypto asset insurance will be regulated, as well as how it will be implemented, by assessing existing insurance laws and the implementation of crypto asset insurance in the United States, United Kingdom, and Canada. This paper uses normative legal research because it will mostly be based on doctrine, existing laws and other legal documents. Before being marketed, the insurance product itself must meet the requirements set out in Financial Services Authority Regulation Number 23 of 2015 and Financial Services Authority Circular Letter Number 13 of 2016 concerning Insurance Product Reports for Insurance Companies